The impact of news on US household inflation expectations - Shih-Kang Chao; Wolfgang Karl Härdle; Jeffrey R. Sheen; Stefan Trück; Ben Zhe Wang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
Analysis of monthly disaggregated data from 1978 to 2016 on US household in ation expectations reveals that exposure to news on in ation and monetary policy helps to explain in ation expectations. This remains true when controlling for household personal characteristics, their perceptions of the e ectiveness of government policies, their expectations of future interest rates and unemployment, and their sentiment levels. We nd evidence of an asymmetric impact of news on in ation expectations particularly after 1983, with news on rising in ation and easier monetary policy having a stronger e ect in comparison to news on lowering in ation and tightening monetary policy.
Keywords: D83; D84; E31; 330; Inflation expectations; news impact; forecast disagreement